Study of Propagation Mechanisms in Dynamical Railway Environment to Reduce Computation Time of 3D Ray Tracing Simulator. (21st May 2013) - Hairoud, Siham; Combeau, Pierre; Pousset, Yannis; Cocheril, Yann; Berbineau, Marion; Vauzelle, Rodolphe
Abstract : In order to better assess the behaviours of the propagation channel in a confined environment such as a railway tunnel for subway application, we present an optimization method for a deterministic channel simulator based on 3D ray tracing associated to the geometrical optics laws and the uniform theory of diffraction. This tool requires a detailed description of the environment. Thus, the complexity of this model is directly bound to the complexity of the environment and specifically to the number of facets that compose it. In this paper, we propose an algorithm to identify facets that have no significant impact on the wave propagation. This allows us to simplify the description of the geometry of the modelled environment by removing them and by this way, to reduce the complexity of our model and therefore its computation time. A comparative study between full and simplified environment is led and shows the impact of this proposed method on the characteristic parameters of the propagation channel. Thus computation time obtained from the simplified environment is 6 times lower than the one of the full model without significant degradation of simulation accuracy.